2012
DOI: 10.1177/0954406212440672
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and prediction of springback in rotary-draw tube bending process using finite element method

Abstract: Rotary-draw tube bending operation is one of the most universal methods used for the tube forming processes. Similar to the other forming methods, some problems such as wall thinning, cross-section distortion, wrinkling, and springback can also be seen on the tubes formed by rotary-draw bending operations. Springback is a very common problem and its prediction plays a crucial role in increasing the efficiency of the tube bending operations and also to overcome the difficulties in the assembly processes. Tube d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…[3][4][5] To solve the springback defects in MPF and other forming process, many scholars worldwide have conducted research on the springback prediction and compensation. 6,7 In theory, N'jock et al 8 proposed an advanced model formulated in the framework of non-associative plasticity to accurately predict the springback of advanced high strength steels material. Liu et al 9,10 calculated the residual stress distribution in thick plate, and proposed an effective method to evaluate the springback in MPF.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] To solve the springback defects in MPF and other forming process, many scholars worldwide have conducted research on the springback prediction and compensation. 6,7 In theory, N'jock et al 8 proposed an advanced model formulated in the framework of non-associative plasticity to accurately predict the springback of advanced high strength steels material. Liu et al 9,10 calculated the residual stress distribution in thick plate, and proposed an effective method to evaluate the springback in MPF.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,6 However, studies for 3D variable curvature bent tube have not been well developed, which are new challenges for the precision-forming technology.…”
Section: Introductionmentioning
confidence: 99%
“…Current research in springback of tube bending mainly focuses on the plane constant curvature axis tube with hot or cold bending, combined with advanced computer numerical control (CNC) tube-bending technology. 3,5,6 However, studies for 3D variable curvature bent tube have not been well developed, which are new challenges for the precision-forming technology.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al 10 revealed the nonlinear springback characterization and behaviors of high strength Ti-3Al-2.5V tube by finite element (FE) analysis. Also by the FE analysis, the geometry-dependent springback behaviors of thin-walled Al-alloy 6061-T4 tube on rotary draw bending were revealed by Li et al 11 Sözen et al 12 addressed the springback phenomena of steel tube NC bending under the interactions between the geometrical and mechanical parameters and developed a surrogate model to predict fast the springback for a given combination of parameters. Using the numerical simulation, Zhan et al 13 investigated the springback mechanism for larger-diameter thin-walled CT20 Ti-alloy tube and proposed a two-level springback compensation method.…”
Section: Introductionmentioning
confidence: 99%